#RecursionFTW. Issue 2 (3rd April 2022) - Ciba, Daniel
ABSTRACT: This essay documents my expansions on a lesson developed in courses that juxtaposed performance and memory studies. Building on a recursive reading of Toni Morrison's literary conceptualisation of rememory, I describe the reiterative nature of memory using two digital performances – a TikTok meme featuring 50 Cent's 'Candy Shop' and a Reddit thread featuring a series of bird paintings. These performances made before the 2020 pandemic show the potentials of collectively inspired art created as virtual media.